Food for Thought: A Systematic Review and Meta‐Analysis on the Effects of Ultra‐Processed Foods on Cognition in Children and Adolescents - Lan Nguyen; Jared Walters; Bernadette Spies; Amelia Coppus; Jenaya Massie; Thamiris Penteado Bertonha (Food Frontiers)
ABSTRACT In the current economic climate, rising costs of unprocessed and organic foods have driven many families toward more affordable alternatives—particularly processed and ultra‐processed foods (UPFs) such as sugar‐sweetened beverages, instant noodles, sweet/salty snacks, and processed meats. Despite their convenience, UPFs provide minimal nutritional value, which may hinder cognitive development, particularly in childhood and adolescence. Given the recent surge of studies within this field, this systematic review and meta‐analysis synthesized existing research to evaluate the link between UPF consumption and cognitive development in youths (children and adolescents). A comprehensive search identified 35 relevant studies encompassing 84,062 participants. Increased UPF consumption was consistently associated with poorer cognitive performance in both children and adolescents across most cognitive domains, including attention, executive functioning, fluid intelligence, language, and visuospatial ability. No significant associations were found between UPF consumption and both memory and processing speed, potentially due to a limited number of studies exploring these outcomes, thereby warranting further investigation. Moreover, consumption of energy drinks, salty snacks, and a combination of UPFs (food and drinks) consistently yielded the strongest negative mean effect sizes across most cognitive domains, indicating that these UPFs are linked with poorer cognitive performance in youths. These findings emphasize the need for dietary interventions aimed at reducing UPF consumption to support optimal cognitive development in children and adolescents. Additionally, the results provide valuable insights to inform public health policies, highlighting the importance of promoting healthier dietary choices and implementing education campaigns to mitigate the cognitive risks associated with UPF consumption.